2022
DOI: 10.3389/fnagi.2022.990567
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative hyperglycemia is associated with elevated risk of perioperative ischemic stroke in type 2 diabetic patients undergoing non-cardiovascular surgery: A retrospective cohort study

Abstract: BackgroundDiabetes mellitus (DM) has been reported to be associated with perioperative stroke, but the effects of preoperative hyperglycemia on the risk of perioperative stroke in diabetic patients undergoing non-cardiovascular surgery remain unclear. This study investigated the association between preoperative hyperglycemia and the risk of perioperative ischemic stroke in type 2 diabetic patients undergoing non-cardiovascular surgery.MethodsThis retrospective cohort study screened 27,002 patients with type 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Till now, no consensus on the controlled target of preoperative or perioperative glucose level has been reached, some guidelines recommend perioperative glucose value below 10 mmol/L or between 6 and 10 mmol/L to avoid hyperglycemia or hypoglycemia (Dhatariya et al 2012 ; Cosson et al 2018 ; Association of Anaesthetists of Great Britain and Ireland 2015 ), but the European Society of Anesthesiology guideline recommend no routine preoperative glucose assessment for non-cardiac surgery (Hert et al 2018 ). Many studies reported the threshold values of preoperative glucose for a specific complication after surgery, which showed that the preoperative fasting glucose level of 5.135 mmol/L is the cut-off value to predict mortality within 30 days after neurosurgery (Zhang et al 2023 ), and the level greater than 7 mmol/L can predict the development of stroke within 30 days after non-cardiac surgery (Liu et al 2022 ); in another retrospective study, the preoperative casual blood glucose value of 6.86 mmol/L in non-diabetic patients and 7.92 mmol/L in diabetic patients could predict postoperative myocardial injury in non-cardiac surgery (Punthakee et al 2018 ). In our study, the cut-off value of preoperative fasting glucose was 5.39 mmol/L to predict AKI in non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, no consensus on the controlled target of preoperative or perioperative glucose level has been reached, some guidelines recommend perioperative glucose value below 10 mmol/L or between 6 and 10 mmol/L to avoid hyperglycemia or hypoglycemia (Dhatariya et al 2012 ; Cosson et al 2018 ; Association of Anaesthetists of Great Britain and Ireland 2015 ), but the European Society of Anesthesiology guideline recommend no routine preoperative glucose assessment for non-cardiac surgery (Hert et al 2018 ). Many studies reported the threshold values of preoperative glucose for a specific complication after surgery, which showed that the preoperative fasting glucose level of 5.135 mmol/L is the cut-off value to predict mortality within 30 days after neurosurgery (Zhang et al 2023 ), and the level greater than 7 mmol/L can predict the development of stroke within 30 days after non-cardiac surgery (Liu et al 2022 ); in another retrospective study, the preoperative casual blood glucose value of 6.86 mmol/L in non-diabetic patients and 7.92 mmol/L in diabetic patients could predict postoperative myocardial injury in non-cardiac surgery (Punthakee et al 2018 ). In our study, the cut-off value of preoperative fasting glucose was 5.39 mmol/L to predict AKI in non-cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2011 study of 529,059 patients undergoing non‐cardiac, non‐neurosurgical procedures, age >61 years was identified as the strongest independent risk factor for peri‐operative stroke, followed by myocardial infarction within 6 months, acute renal failure or pre‐existing dialysis, prior stroke/transient ischaemic attack, hypertension, chronic obstructive pulmonary disease and smoking 3 . Other studies have supported these findings, 2,5–8 as well as identifying diabetes mellitus and hyperglycaemia, 7,9 current or prior atrial fibrillation, 7,10,11 congestive heart failure, 2,7 valvular heart disease, 7 renal disease, 7 coronary artery disease, 12 cancer, patent foramen ovale 4,13 and migraine 14 as independent risk factors for peri‐operative stroke 2,7,8,13 . Additionally, the impact of pre‐existing medications, such as statins 15 and acetylsalicylic acid, 16,17 has also been studied in relation to peri‐operative stroke with generally inconclusive results, along with ramifications of intra‐operative management strategies, none of which clearly demonstrates superiority.…”
Section: Introductionmentioning
confidence: 92%